Jewish extremist and terrorist organizations in Israel - A. V. Krylov (Международная аналитика, 2017)
This article is an extension of the research material published in the previous issue of the Journal “International Analytics” (2016, vol. 3 (17), p. 45–58), and focused on the activity of the Jewish paramilitary groups in Palestine before the establishment of the State of Israel in 1948. Originally the conspiratorial Jewish extremist organization opposed the policy of the Jewish immigration restraint which had been carried out by the socialist countries, especially the USSR. Some ultra-Orthodox groups, such as the Union of Zealots, used openly the terrorist methods in the struggle against the development of Israel as a secular and democratic state. After the war of 1967 and the Israeli occupation of the Arab territories the orthodox-nationalists, who formed the vanguard of the “Movement for Greater Israel”, created an underground network of extremist armed organizations. From the beginning, the activities of these groups were contrary to the Israeli Law on the Fight against Terror. The term commonly used for the Jewish underground groups in Hebrew is “mahteret”. There have been several dozen groups of this kind in the history of the Israeli settlements movement. The most famous of them are “Kach” (“Thus”) and “Kahane Chai” (“Kahane Lives”).The initiator and inspirer of the “Jewish Underground” was an American Orthodox Rabbi Meir Kahane. He founded a political settlement party “Kach” which had legally existed until in 1988 a ban on the list of its candidates in the parliamentary elections was imposed by the Supreme Court of Israel because of the accusations of the denial of the democratic character of the state of Israel and the promotion of racism. The activities of both organizations were declared terrorist and banned in the USA and some other countries.The article analyses religious, philosophical and political routes of the modern ideology of Israeli orthodox nationalists who participate in the settlement movement on the occupied Arab territories as well as the illegal activities of the most famous parties and organizations supporting the policy of the extension of the Israeli jurisdiction over the occupied Arab territories.